2016
DOI: 10.1093/annonc/mdv609
|View full text |Cite
|
Sign up to set email alerts
|

Vinflunine–gemcitabine versus vinflunine–carboplatin as first-line chemotherapy in cisplatin-unfit patients with advanced urothelial carcinoma: results of an international randomized phase II trial (JASINT1)

Abstract: This randomized phase II study examined the use of vinflunine in combination with gemcitabine or carboplatin as first-line chemotherapy in cisplatin-ineligible patients with advanced urothelial carcinoma. Both doublets were feasible and offered a similar 77% disease control rate. Response rate (44%), overall survival (14 months) and less haematological toxicity favoured vinflunine–gemcitabine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
26
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 22 publications
6
26
0
7
Order By: Relevance
“…No definite treatment‐related death was recorded, but one patient had fatal pulmonary embolism (unlikely relation to study treatment). Overall, the AEs are in line with previous studies combining vinflunine and other cytotoxic agents .…”
supporting
confidence: 88%
“…No definite treatment‐related death was recorded, but one patient had fatal pulmonary embolism (unlikely relation to study treatment). Overall, the AEs are in line with previous studies combining vinflunine and other cytotoxic agents .…”
supporting
confidence: 88%
“…Furthermore, the efficacy of vinflunine in second-line treatment has been confirmed in real-world studies [15]. Vinflunine combinations, vinflunine and gemcitabine (VG) versus vinflunine and carboplatin, were explored as first-line treatment for cisplatin-unfit patients in the randomised phase II trial JASINT1 [16], showing promising response rates and survival (ORR 53% with confirmed ORR 44% and mOS 14.0 months in the VG arm), although the trial did not include a non-investigational control arm. Based on available data on vinflunine as second-line treatment in patients with aUC and the potential benefit of vinflunine combination therapy as first-line treatment, we explored the efficacy of VG versus standard chemotherapy with CG in the randomised phase II VINGEM trial in patients with aUC unfit for cisplatin due to renal impairment.…”
Section: Introductionmentioning
confidence: 99%
“…44 De Santis et al investigated a non-carboplatin regimen, vinlunine-gemcitabine, versus vinfluninecarboplatin in the JASINT1 trial. 45 Both doublets offered similar PFS (5.9 versus 6.1 months respectively) and OS (14 versus 12.8 months)…”
Section: Chemotherapy For Advanced Urothelial Cancermentioning
confidence: 93%